Research in the wild(s): Opportunities, affordances and constraints doing assistive technology field research in underserved areas - Bellucci, Andrea; Nolan, Jason; Di Santo, Aurelia (Disability Studies Quarterly, 2018)
The particular needs of disabled children in the 'Majority World' is under researched. There is an assumption that children's needs are the same as those supported by well-developed healthcare infrastructures. Field research is necessary to understand the design challenges, opportunities and affordances for these children. For research and design to meet their unique needs, processes must start with children in their own communities. AAC (Alternative and Augmentative Communication) technology design rarely benefits from early stage in situ fieldwork. We report on the conceptualization, development and lessons learned from field research surrounding our AAC device, we call the RE/Lab Comunicación Aumentada Móvil (Mobile Augmented Communication) device, developed specifically for disability design fieldwork with indigenous communities in Cochabamba, Bolivia. Our device is part of Diseñando para el Futuro (Designing for the Future), which is supporting the indigenous community in the creation of custom adaptations for disabled children in Cochabamba. In order to ascertain design requirements of AAC devices and applications for such communities, we took our prototype AAC device into the field as both a tool 'in development' and as a communication artifact to enable us to understand the needs of these children. The project PI (an Autistic self-advocate) situates research practice within the 'nothing about us without us' paradigm, accordingly, project goals are to work with children to create communication tools to help them express their goals, interests and needs and enable the co-creation of new tools with them.